Understanding human agency - Mayr, Erasmus (Oxford University Press, 2011)
How can we be active agents when processes in the world are explicable by the laws of natural science? Erasmus Mayr explores this deep-running tension in our self-understanding and develops a new agent-causal solution to the conflict. He argues that actions explained by aims and reasons are compatible with a scientific view of the universe.